Eucaristia e pobres em Francisco Taborda. - Galindo, João Paulo Gomes (2019)
This dissertation has Eucharist and the poor as its main theme. Through a bibliographical analysis, it seeks to ascertain the consistency of the essential relationship between the Eucharist and the poor according to Francisco Taborda's work. The dissertation is divided into three chapters. In the first chapter, attention is drawn to the essential relationship between the Church and the Eucharist: "Church as Community of Faith", "Sacraments of Faith", "Eucharist - Mystery of Faith". In the second chapter, we seek to understand the centrality of the poor in the life and mission of the Church, a fundamental characteristic of the Latin American theology of the sacraments, explaining the relationship between Jesus and the poor and, consequently, between the Church and the poor. In the third chapter, we seek to clarify the essential link between the Eucharist and the poor, explaining in what sense the Eucharist is the fulfillment and promise of salvation, school of life and bread for the poor. This is intended to contribute to a profound Eucharistic experience in the communities and to feed the hope of suffering humanity.